2009
DOI: 10.1111/j.1476-4431.2009.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Critical illness‐related corticosteroid insufficiency in a dog with septic shock

Abstract: This case is the first published report of hydrocortisone-responsive hypotension and transient CIRCI associated with naturally occurring septic shock in a dog.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Treatment regimens have been published primarily in case reports, reviews, and book chapters, with no reliable clinical trial data available in veterinary species. A single case report in a dog with pressor‐refractory septic shock describes the use of hydrocortisone 0.5 mg/kg IV q6h to treat suspected CIRCI . Pressors were discontinued within hours of starting the hydrocortisone, and the steroid dose was tapered over many days beginning 4 days after pressor independence.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment regimens have been published primarily in case reports, reviews, and book chapters, with no reliable clinical trial data available in veterinary species. A single case report in a dog with pressor‐refractory septic shock describes the use of hydrocortisone 0.5 mg/kg IV q6h to treat suspected CIRCI . Pressors were discontinued within hours of starting the hydrocortisone, and the steroid dose was tapered over many days beginning 4 days after pressor independence.…”
Section: Treatmentmentioning
confidence: 99%
“…For individuals that recover from the acute or critical illness, prognosis for return of normal HPA axis function following an episode of CIRCI is very good …”
Section: Prognosismentioning
confidence: 99%
“…The condition has also been reported in humans [57,58] and dogs [59][60][61] with acute critical illness, severe sepsis, and septic shock. Several studies suggested that RAI or CIRCI may occur in septic neonatal foals: one case report of transient HPA axis dysfunction in a septic neonatal foal was described [62], and three independent studies measured basal ACTH and cortisol concentrations in healthy and septic foals and found significantly increased ACTH-to-cortisol ratio in nonsurviving septic foals [63][64][65].…”
Section: Critical Illness-related Corticosteroid Insufficiencymentioning
confidence: 85%
“…Previous reports of treatment of suspected CIRCI in veterinary medicine include a dog with hydrocortisone‐responsive septic shock and a cat with polytrauma‐related hypotension responsive to intravenous dexamethasone . Additionally, one abstract reports a prospective blinded placebo‐controlled study in eight dogs treated with either hydrocortisone or an equivalent volume of saline, but results were inconclusive due to the small number of dogs enrolled .…”
Section: Discussionmentioning
confidence: 99%